The effect of exopolysaccharides from EMS-induced Porphyridium cruentum mutant on human epidermal and dermal layers - Han, Sang-Il; Heo, Young Mok; Jeon, Min Seo; Kyung, Seoyeon; Kang, Seunghyun; Kwon, Soon-Jae; Ryu, Jai Hyunk; Kim, Jae Hoon; Ahn, Joon-Woo (Frontiers in Marine Science, 2024)
In microalgae biotechnology, Porphyridium cruentum is valued for its phycobiliproteins and exopolysaccharides. In this study, we developed a mutant of P. cruentum LIMS-PS-1061 through ethyl methanesulfonate mutagenesis and colony screening. The mutant showed a 33.9% increase in dry weight compared to the wild type under white light. Notably, the mutant maintained the total pigment amount, but with changes in specific components; the chlorophyll content decreased 2.20- and 3.61-fold under white and blue light respectively, compared to the wild type, while phycobiliproteins increased 1.59- and 1.23-fold under the same conditions. This suggests compensation for photosynthetic capacity through alterations in pigment composition. In addition, P. cruentum's exopolysaccharides upregulated genes related to skin moisturization, barrier enhancement, and elasticity improvement, and promoted wound healing through fibroblast migration. We proposed a skin condition improvement mechanism of P. cruentum's exopolysaccharides on human skin by integrating the individual skin care mechanisms of aquaporin 3, filaggrin, involucrin, loricrin, elastin, and fibrillin-1. These findings open the industrial applications of P. cruentum's phycobiliproteins and exopolysaccharides and suggest a role for P. cruentum's exopolysaccharides in improving human skin conditions.